2016
DOI: 10.1111/ipd.12238
|View full text |Cite
|
Sign up to set email alerts
|

Children's experiences of dental anxiety

Abstract: Background Dental anxiety is common among children. Although there is a wealth of research investigating childhood dental anxiety, little consideration has been given to the child's perspective. Aim This qualitative study sought to explore with children their own experiences of dental anxiety using a cognitive behavioural therapy assessment model. Design Face‐to‐face, semi‐structured interviews were conducted with dentally anxious children aged 11–16 years. The Five Areas model was used to inform the topic gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 29 publications
6
88
1
3
Order By: Relevance
“…The concern that some interventions generate greater anxiety than others and that this anxiety can lead to negative behaviour was not identified in the age group analysed. Previous studies have investigated the type of procedure and children's perceptions regarding dental treatment, but the assessment of behaviour and dental anxiety is limited since there is no comparison in both invasive procedures as endodontic treatment and dental extraction, making it difficult to compare the present results to previous findings …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The concern that some interventions generate greater anxiety than others and that this anxiety can lead to negative behaviour was not identified in the age group analysed. Previous studies have investigated the type of procedure and children's perceptions regarding dental treatment, but the assessment of behaviour and dental anxiety is limited since there is no comparison in both invasive procedures as endodontic treatment and dental extraction, making it difficult to compare the present results to previous findings …”
Section: Discussionmentioning
confidence: 92%
“…The same number of children had negative behaviour during both invasive dental procedures, whereas none of the patients in the control group (prophylaxis and topical fluoride) had negative behaviour. Invasive procedures cause more aversive behaviour due to the fear that treatment will be painful, will involve forceful movements and discomfort, and will require anaesthesia …”
Section: Discussionmentioning
confidence: 99%
“…[1678] It is also related to many factors such as personality characteristics, a history of traumatic dental experience, painful dental experience in childhood, or even from indirect learning from dentally anxious peers or family members. [910111213]…”
Section: Introductionmentioning
confidence: 99%
“…The more complex the dental treatment, the more negative the behaviour tends to be . In the qualitative study of Morgan, children who experienced dental local anaesthesia reported a specific trait of anxiety externalized as “painful to bear,” reinforcing the influence of clinical context on child behaviour. In the present study, the association between social, emotional, and behavioural problems and the behaviour in the dental setting remained even after adjustments for age, child dental fear, maternal anxiety, and complexity of dental treatment, indicating that mental disorders may also influence the child behaviour during dental treatment.…”
Section: Discussionmentioning
confidence: 99%
“…When these children come to dental settings, both the dentist and the family should be prepared to deal with such difficulties. Children may present with difficult behaviour to manage due to a series of well‐known established factors, such as parental characteristics, clinical procedures (eg, use of injection for local anaesthesia), pain, negative previous dental experience, and other psychosocial characteristics of children, such as dental anxiety/fear . Only more recently have studies drawn attention to psychological characteristics and their association with the behaviour of children during dental treatment.…”
Section: Introductionmentioning
confidence: 99%